Civic Education in European States: the Aspect of Education for Democracy - Ema Klemenčič (Anali Hrvatskog Politološkog Društva, 2006)
Realistically speaking, it is impossible to discuss a unifi ed model of education for democracy, since no model encompasses the various dimensions of that which we call ‘education for democracy’. In public discourse there are several documents attempting to defi ne the said concept. To some extent they are merged into the so-called concept of education for democratic citizenship (the Council of Europe Programme). Likewise the education of a European citizen is one of the central points of common educational trends in EU documents. There are, in fact, only two approaches. Since one cannot even speak of a model in the theoretical sense, it would be quite irresponsible to try and speak of it in the practical sense, which is why we attempt here to focus on a single aspect, namely, civic education in schools.